Beyond Territoriality: Assessing the Effectiveness of the Madrid System for Trademark Protection in Indonesia - Ni Ketut Supasti Dharmawan; Made Suksma Prijandhini Devi Salain; Putu Aras Samsithawrati; Annalisa Yahanan (Sriwijaya Law Review, 2026)
Registered trademark protection is territorial, granting legal rights only within the jurisdiction where the mark is registered. To overcome this limitation, the WIPO administers the Madrid System, which allows trademark owners to obtain protection in multiple member countries through a single international application. Indonesia has adopted this system through Law No. 20 of 2016. However, its utilisation by Indonesian trademark owners remains relatively low. This study examines the benefits of the Madrid System for Indonesian trademark owners in accessing global markets and analyses the challenges that hinder its effective use. Employing a socio-legal research method, the study finds that the Madrid System offers clear advantages, including administrative efficiency through a single application filed in one language, centralised management by WIPO, and cost savings through the payment of one set of fees in a single currency. Despite these benefits, several obstacles limit participation. These include low public awareness of international trademark registration, high registration costs that disproportionately affect micro, small, and medium enterprises, and limited English-language proficiency among applicants. A further significant concern is the risk of a "central attack," whereby the refusal or cancellation of the basic Indonesian application within the first five years may invalidate all corresponding international registrations. Additionally, weak inter-institutional coordination and the absence of measurable policy indicators undermine effective implementation. The study underscores the need for stronger government intervention to enhance national trademark registration and to improve public understanding of the strategic importance of international trademark protection.